Identifying Critical 21st-Century Skills for Workplace Success: A Content Analysis of Job Advertisements. (March 2020) - Rios, Joseph A.; Ling, Guangming; Pugh, Robert; Becker, Dovid; Bacall, Adam
This article extends the literature on 21st-century learning skills needed for workplace success by providing an empirical examination of employers' direct communication to potential employees via job advertisements. Our descriptive analysis of 142, 000 job advertisements provides two contributions. First, this is one of the first studies to empirically rank-order skill demand. In doing so, it is clear that oral and written communication, collaboration, and problem-solving skills are in high demand by employers, with particular emphasis on the pairing of oral and written communication. Furthermore, it is apparent that many of the skills suggested in the literature as being critical for workplace success are in very low demand by employers, and some were not found to be mentioned at all (e.g., social responsibility). Second, this study explicitly examined whether 21st-century skill demand varied by job characteristics, which was found to be the case, with differences being noted for both education level and degree field requirements. Results were replicated with a sample of roughly 120, 000 job advertisements collected 1 year from the initial data collection. Implications for developing educational standards around 21st-century skill development are discussed.